Systems Approaches to Unravel Molecular Function: High-content siRNA Screen Identifies TMEM16A Traffic Regulators as Potential Drug Targets for Cystic Fibrosis. Issue 5 (15th March 2022) - Pinto, Madalena C.; Botelho, Hugo M.; Silva, Iris A.L.; Railean, Violeta; Neumann, Beate; Pepperkok, Rainer; Schreiber, Rainer; Kunzelmann, Karl; Amaral, Margarida D.
Graphical abstract: Highlights: Some CF patients (∼20%) are not eligible for highly effective CFTR modulator drugs. An attractive 'by-pass' therapy for CF is to stimulate non-CFTR chloride channels. A high-content siRNA screen revealed 262 modulators of TMEM16A channel traffic. Hit validation shows that ADRA2C and CXCR3 knock-down boosts TMEM16A Cl − secretion. Inhibiting these two TMEM16A modulators is a potential therapeutic strategy for CF. Abstract: An attractive approach to treat people with Cystic Fibrosis (CF), a life-shortening disease caused by mutant CFTR, is to compensate for the absence of this chloride/bicarbonate channel by activating alternative (non-CFTR) chloride channels. One obvious target for such "mutation-agnostic" therapeutic approach is TMEM16A (anoctamin-1/ANO1), a calcium-activated chloride channel (CaCC) which is also expressed in the airways of people with CF, albeit at low levels. To find novel TMEM16A regulators of both traffic and function, with the main goal of identifying candidate CF drug targets, we performed a fluorescence cell-based high-throughput siRNA microscopy screen for TMEM16A trafficking using a double-tagged construct expressed in human airway cells. About 700 genes were screened (2 siRNAs per gene) of which 262 were identified as candidate TMEM16A modulators (179 siRNAs enhanced and 83 decreased TMEM16A traffic), being G-protein coupled receptors (GPCRs) enriched on the primary hit list. Among the 179 TMEM16A traffic enhancer siRNAs subjected to secondary screening 20 were functionally validated. Further hit validation revealed that siRNAs targeting two GPCRs – ADRA2C and CXCR3 – increased TMEM16A-mediated chloride secretion in human airway cells, while their overexpression strongly diminished calcium-activated chloride currents in the same cell model. The knockdown, and likely also the inhibition, of these two TMEM16A modulators is therefore an attractive potential therapeutic strategy to increase chloride secretion in CF.